Impact of Personal Data Protection (PDP) Law and Enforcement Authority Body for PDP Failure in Banking Industry - Ignatius Widhianto; Lastuti Abubakar; Tri Handayani (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
Personal Data Protection law (PDP) as enacted on 17th October 2022 is create new dimension in Indonesia legal system. PDP law not only “cherry on top” of the previous regulation, but also to perfection the law that focus on protection of the personal or individual rights, especially if that person is bank customer. Financial services is one of the most highly regulatory industry, banking industry as the part of financial services industry have holy grail obligation to protect as we called bank secrecy. PDP law is to complement bank secrecy regulation, since PDP provide specific and strict regulation regarding personal data processing activities in banking. Until February 2026, PDP law not have an implementation regulation and specific regulator as mentioned before at law, this condition can raise the challenge for the banking industry to comply. Banking industry is an industry that process personal data in large number, this industry shall to response the situation carefully, since Bank DNA must compliance with the prevailing law and regulations, unfortunately the regulation not yet enough regulate personal data protection in detail. Moreover, PDP law mandates the creation of a special intuitions related to the regulator and enforcement of PDP Law infringement. The creation of this institution can raise dualism for banking industry, considering that banking is already regulated and supervised by the Financial Services Authority (OJK).